Integrasi Pembelajaran IPS pada Kurikulum 2013 di Sekolah Dasar - Tika Meldina; Melinedri Melinedri; Alfiana Agustin; Siti Hadijah Harahap (Institut Agama Islam Negeri (IAIN) Curup, 2020)
This research wanted to find out the integration of social studies learning in the curriculum of 2013 in elementary schools. In structure’s curriculum of elementary school/ madrasah ibtidaiyah, social studies are only studied in the high class (IV, V, VI). In the low class (I, II, III) the name of the social studies is eliminated, but Basic Competence of social studies is integrated into the basic competence of other subjects such as Indonesian, Pancasila and Citizenship Education and Mathematics are linked through the closeness of meaning. In the high class, sosial studies have same position as other subjects. Even though learning is done thematically, basic competence for social studies remains independent. The approaches used in integrating social studies learning include indisciplinary, interdisciplinary and multidisciplinary integration.